EVALUASI DAN PENGEMBANGAN KURIKULUM S1 TEKNIK SIPIL DI ERA DISRUPSI BERBASIS STAKEHOLDERS EKSTERNAL - Umniyah Salma Fathin (Universitas Pendidikan Indonesia (UPI), 2023)
This research aims to obtain information about: (1) evaluation of the curriculum of the Bachelor of Civil Engineering study program in general based on stakeholders external Outcomes Based Curriculum in Disruption Era (OBCiDE); (2) development of the curriculum for the Bachelor of Civil Engineering Study Program, FT UNY, based on input from stakeholders external Outcomes Based Curriculum in Disruption Era (OBCiDE). This research is qualitative research that uses a descriptive approach. Sources of data obtained are primary data and secondary data. The research method used is Focus Group Discussion and documentation. The data analysis approach used was (1) data collection, (2) data reduction, (3) data verification, and (4) drawing conclusions. The results of this research indicate that there is a need increasing the content and scope of the Bachelor of Civil Engineering curriculum with reference to OBCiDE which includes: (1) utilization of software, especially Building Information Modeling and SAP S/4HANA and (2) facilitation of final and fresh graduates in obtaining a Work Skills Certificate as a companion certificate for a diploma. In addition, it is necessary to develop a curriculum for the Bachelor of Civil Engineering study program, FT UNY, with reference to OBCiDE based on Stakeholders External which includes:(1) participating with PT Wika in engineering, (2) lecturers accompanying internship students in projects, and (3) collaborating with Intakindo in introducing BIM to lecturers.